2020
DOI: 10.1371/journal.pone.0234012
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-specific characterization of breast cancer invasion using a microfluidic tumor platform

Abstract: Understanding progression of breast cancers to invasive ductal carcinoma (IDC) can significantly improve breast cancer treatments. However, it is still difficult to identify genetic signatures and the role of tumor microenvironment to distinguish pathological stages of preinvasive lesion and IDC. Presence of multiple subtypes of breast cancers makes the assessment more challenging. In this study, an in-vitro microfluidic assay was developed to quantitatively assess the subtype-specific invasion potential of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…For the experiments, the MCF-7 breast cancer cell line was used. This cell line is characterized by the Luminal A subtype expressing estrogen receptor (ER) and progesterone receptor (PR) [ 15 ]. The luminal-A is the most common subtype and represents 50–60% of all breast cancers [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the experiments, the MCF-7 breast cancer cell line was used. This cell line is characterized by the Luminal A subtype expressing estrogen receptor (ER) and progesterone receptor (PR) [ 15 ]. The luminal-A is the most common subtype and represents 50–60% of all breast cancers [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies on microfluidic cell culture technology in the literature pointed out different aspects of cancer modeling, including cancer cell invasion [ 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 ], intravasation [ 284 , 285 ], extravasation [ 286 , 287 , 288 ], and tumor microenvironment modeling [ 289 , 290 ]. Cell invasion refers to cell motility, including attachment, proteolysis, and relocation of cancer cells, which may result in cancer metastasis [ 291 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Using a vascularized microfluidic chip, it was shown that MDA-MB-231 breast cancer cells invaded paracellularly by disrupting the endothelial junction, whereas HepG2 liver cancer cells invaded through the transcellular process [29]. Using another in vitro model of an invasive ductal carcinoma (IDC)-on-a-chip model that was developed using viscous fingering method, invasive characteristics of different human breast cancer cell lines were identified [30]. Breast cancers have been classified into different subtypes by their different gene expression profiles, which include luminal A, luminal B, hormone epidermal growth factor receptor 2 (HER-2) enriched, basal-like, and triplenegative breast cancer (TNBC) type.…”
Section: Use Of Endothelium-based Modelsmentioning
confidence: 99%